Lehninger principles of biochemisty - Nelson, David L.; Cox, Michael M. Professor of Biochemistry; Hoskins, Aaron A. Associate Professor of Biochemistry (Macmillan International, 2021)
Lehninger Principles of Biochemistry earned acclaim for its presentation and organisation of complex concepts and connections, anchored in the principles of biochemistry. This legacy continues in the eight edition with a new framework that highlights the principles and supports student learning